197k views
0 votes
I need to solve 12r-6s=t for r

User Lotta
by
4.8k points

2 Answers

2 votes

Answer:

Simplifying

12r + -6s = t

Solving

12r + -6s = t

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '6s' to each side of the equation.

12r + -6s + 6s = 6s + t

Combine like terms: -6s + 6s = 0

12r + 0 = 6s + t

12r = 6s + t

Divide each side by '12'.

r = 0.5s + 0.08333333333t

Simplifying

r = 0.5s + 0.08333333333t

Explanation:

sorry if this doesnt help

User Shanina
by
5.0k points
6 votes

Answer:

r=s/2+t/12

Explanation:

To find the answer, add 6s to both sides to get 12r=6s+t. Divide both sides by 12 to get the answer.

User JFAP
by
5.0k points